1988
DOI: 10.1002/mc.2940010205
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression during two‐stage mouse skin carcinogenesis of a type 147‐kDa keratin, k13, normally associated with terminal differentiation of internal stratified epithelia

Abstract: Specific keratin cDNA probes and monospecific antikeratin antisera were used to analyze mouse epidermis and epidermal tumors for the expression of a type I 47-kDa keratin, K13, normally associated with terminal differentiation of internal stratified epithelia. We demonstrated that this keratin was virtually absent from the entire body epidermis at various stages of development. Also, it was not detected in various forms of acute and chronic epidermal hyperproliferation or in epidermal cells cultured under cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 55 publications
1
66
1
Order By: Relevance
“…2). In contrast, strongly positive immunofluorescence staining for K13, a malignancy marker in squamous epithelia (32), was observed in tumors classified as SCCs from both Smad3 ϩ/ϩ and Smad3 ϩ/Ϫ mice, but not in tumors from Smad3 Ϫ/Ϫ mice ( Fig. 2), further confirming that the tumors from the Smad3 Ϫ/Ϫ mice were benign papillomas.…”
Section: Smad3 Knockout Mice Exhibited Reduced Tumor Formation and Mamentioning
confidence: 66%
“…2). In contrast, strongly positive immunofluorescence staining for K13, a malignancy marker in squamous epithelia (32), was observed in tumors classified as SCCs from both Smad3 ϩ/ϩ and Smad3 ϩ/Ϫ mice, but not in tumors from Smad3 Ϫ/Ϫ mice ( Fig. 2), further confirming that the tumors from the Smad3 Ϫ/Ϫ mice were benign papillomas.…”
Section: Smad3 Knockout Mice Exhibited Reduced Tumor Formation and Mamentioning
confidence: 66%
“…normally associated with the terminal differentiation of internal stratified epithelia. has been reported in mouse skin tumours (Nischt et al 1988). …”
Section: Resultsmentioning
confidence: 93%
“…As expected, expression of the hyperproliferation-associated keratin K6 apperared highly induced in a continuous pattern in both transgenic and control tumors (Figure 7a and b). Aberrant expression of keratin K13, a marker for progression in mouse skin carcinogenesis (Nischt et al, 1988;Gimenez-Conti et al, 1990), was observed in both types of tumors. At 6 weeks, most transgenic tumors show continuous K13 expression, while control tumors show focal staining (Figure 7c and d).…”
Section: Hyperproliferation-associated Inducibility Of the Transgene mentioning
confidence: 95%